2021
DOI: 10.1177/14680874211008006
|View full text |Cite
|
Sign up to set email alerts
|

Infrared high-speed thermography of combustion chamber wall impinged by diesel spray flame

Abstract: As a demonstration of a new method to examine the extremely unsteady and spatially varying wall heat transfer phenomena on diesel engine combustion chamber wall, high-speed imaging of infrared thermal radiation from the wall surface impinged by a diesel spray flame was attempted using a high-speed infrared camera. A 35 mm-diameter chromium-coated quartz window surface was impinged by a diesel spray flame with an impinging distance of 27 mm from the nozzle orifice in a constant volume combustion chamber. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…These mechanisms are not fully understood, and several recent papers have employed advanced diagnostic techniques to resolve the relationship between heat transfer and the local turbulence in the flow. 1012 A recent study by Srna parallels the current work in that several different injection schedules were investigated in a diesel engine to understand the effect on local heat flux. 13 The experimental data set included fast-response surface temperature measurements of the cylinder liner with simultaneous optical diagnostics of the jet.…”
Section: Introductionmentioning
confidence: 84%
“…These mechanisms are not fully understood, and several recent papers have employed advanced diagnostic techniques to resolve the relationship between heat transfer and the local turbulence in the flow. 1012 A recent study by Srna parallels the current work in that several different injection schedules were investigated in a diesel engine to understand the effect on local heat flux. 13 The experimental data set included fast-response surface temperature measurements of the cylinder liner with simultaneous optical diagnostics of the jet.…”
Section: Introductionmentioning
confidence: 84%
“…The interaction of wall and spray, mainly taking place in the small-bore high-speed diesel engine, not only has significant effects on mixture formation, but also on the combustion, as well as the emission process in the cylinder. In order to clarify the effect of spray impingement, an analysis of the two-dimensional piston cavity, along with flat wall impinging spray flame, is usually performed in a high pressure and temperature constant-volume engine-like combustion chamber [54][55][56][57][58]. As a basis for evaluation, free spray flame is normally also conducted.…”
Section: Spray Atomizationmentioning
confidence: 99%
“…formed in a high pressure and temperature constant-volume engine-like combustion chamber [54][55][56][57][58]. As a basis for evaluation, free spray flame is normally also conducted.…”
Section: Spray Atomizationmentioning
confidence: 99%
“…Combustion chamber characteristics such as bore-to-stroke ratio, compression ratio, and piston bowl geometry are the most important parameters of diesel compression ignition engines because they are directly determining the overall quality of the combustion process and subsequently, the formation and propagation of the flame front. 18 Therefore, optimization of these parameters has attracted the attention of many researchers and design engineers. Choosing an optimal operating point for combustion chamber parameters can reduce harmful engine-out emissions like HC , CO , and PM , and improve fuel economy.The outcomes of vast studies devoted to combustion chamber modifications have shown great potential to achieve low emissions and high performance at the same time.…”
Section: Introductionmentioning
confidence: 99%